ISLAMIC FINANCIAL WISDOM: EXAMINING HIBAH AWARENESS IN ISLAMIC WEALTH MANAGEMENT AMONG MUSLIM COMMUNITIES - Wan Jusoh, Wan Noor Hazlina; Abu Bakar, Muhammad Alif Syazwan (Jurnal ’Ulwan, 2024)
Nowadays, the existence of unclaimed property upon the owner’s death is keep increasing. Hibah is one of estate management planning in Islam, which is not widely practiced by Muslims in this country. Most of Malaysian Muslims do not understand the concept of hibah because of inadequate knowledge plus they do not really expose with the implementation of hibah. Moreover, they are facing difficulties to whom they should refer to manage their property due to the lack of exposure of hibah practice. This research paper aims to explore the level of hibah awareness as an alternative mechanism in Islamic wealth management among Muslim residents in Seremban, Negeri Sembilan. Hence, this study carries out the objective to ascertain the awareness of hibah as an alternative mechanism in Islamic wealth management among Muslim residents in Seremban, Negeri Sembilan. This study used quantitative method with a self-administered questionnaire. Data were collected from 110 respondents of Seremban residents in Negeri Sembilan state. The result shows that most of the respondents have a very excellent and strong awareness of hibah as one of wealth management mechanisms. It is believed that the educational background of the respondents might influence the positive findings.